The theory and practice of grading writing : problems and possibilities - Zak, Frances, 1939-; Weaver, Christopher C., 1962- (State University of New York Press, 1998)
"Grading is one of the thorniest issues writing teachers must deal with, yet, surprisingly little has been written on this topic. As writing teachers move increasingly toward practices that focus on writing as a process, they face a growing need to reconsider their systems of grading to determine whether or not these systems support their pedagogies. The authors interrogate the grading of individual papers as well as portfolios and the assigning of end-of-term grades. This collection explores the issues and problems that have emerged as conventional grading practices have lagged behind and been challenged by new theories of language."--BOOK JACKET. "While the book will be of interest to theorists, Zak and Weaver have also made the book relevant and useful to teachers whose primary interest is the practical consequences of theory in their classrooms. Where theoretical discussion takes place, the language is clear and accessible. Many of the authors write directly from personal experience, telling stories of the classroom or writing of new techniques and approaches they have tried. They speak with the voices of teachers, and the tone and content of their words convey a sense of the immediacy of the topic."--Jacket